PROBLEMS OF PERSON RECOGNITION BASED ON EAR PLUMB IMAGE IN ENSURING SECURITY (Web of Technology: Multidimensional Research Journal, 2023)
This article provides a brief overview of the classification of threats to websites by level. The above information helps us to closely study the threats to websites. The user can anticipate and control threats to websites. It detects and eliminates illegal activities, harmful situations and certain types of risks.